Health Conditions and Functional Status in Adults with Autism: A Cross-Sectional Evaluation - Fortuna, Robert J.; Robinson, Laura; Smith, Tristram H.; Meccarello, Jon; Bullen, Beth; Nobis, Kathryn; Davidson, Philip W. (Journal of general internal medicine : JGIM, 2016)
ABSTRACT BACKGROUND Children and adolescents with autism spectrum disorder (ASD) have many well-known health concerns, yet health conditions in adults with ASD remain poorly defined. OBJECTIVE To examine health conditions and functional status in adults with ASD and identify factors associated with health and functional status across age cohorts. DESIGN AND SUBJECTS We collected cross-sectional data from 255 adult subjects aged 18 to 71 years with ASD using the Rochester Health Status Survey IV (RHSS-IV), a 58-item validated survey instrument. We used the National Health and Nutritional Examination Survey and National Health Interview Survey to provide comparative prevalence rates in the general population. RESULTS Compared to the general population, young adults aged 18–29 with ASD had a substantially higher prevalence of seizure disorder (11.2 % vs. 1.4 %; p = 0.002), depression (16.4 % vs. 6.4 %; p = 0.007), hypertension (12.9 % vs. 6.3 %; p = 0.05), and allergies (39.7 % vs. 8.4 %; p < 0.001). In contrast, young adults with ASD had considerably lower rates of sexually transmitted illness (STI) (0.9 % vs. 4.3 %; p = 0.03), tobacco use (5.2 % vs. 31.9 %; p < 0.001), and alcohol misuse (0.9 % vs. 11.9 %; p < 0.001). Adults 40 and over with ASD also had higher rates of seizure disorder (29.2 % vs. 1.7 %; p < 0.001), lower tobacco use (2.8 % vs. 24.5 %; p < 0.001), and lower alcohol misuse (1.4 % vs. 18.2 %; p < 0.001) compared to the general population. Amongst the 55 % of participants with a documented IQ score, 91 % had an intellectual disability (IQ < 70). Within the cohort aged 40 years old and older, only 54.2 % were independent with eating, 43.0 % independent with dressing, and 43.1 % independent with bathing. Lower IQ and depression were associated with lower functional status. CONCLUSIONS Adults with ASD have a high prevalence of seizure disorders and depression, but low rates of STIs, tobacco use, and alcohol misuse. Within our cohort, the majority of older adults with ASD required some assistance with activities of daily living.